Knowledge, attitudes, and practices related to cystic echinococcosis in an endemic region of Türkiye: A One Health assessment - Selcuk, Muhammed Ahmed; Kandemir, Atilla; Simsek, Sami (Elsevier, 2026)
This study evaluated the knowledge, attitudes, and practices (KAP) related to cystic echinococcosis (CE) among residents of Siirt province, a high-risk area in southeastern T & uuml;rkiye. A cross-sectional community-based survey was conducted with 1000 participants from urban and rural districts using a structured 50-item questionnaire. Composite KAP scores were calculated, and associated factors were examined using bivariate analyses, Spearman correlations, and multivariable logistic regression. Significant urban-rural differences were observed, with urban residents showing better knowledge, more positive attitudes, and safer preventive behaviors than rural residents. These findings highlight the need to place particular emphasis on rural communities, where knowledge gaps and risky practices were more pronounced. Awareness of CE was limited, with only 38.5% of participants having heard of the disease. Median knowledge, attitude, and practice scores were 4 (IQR: 2-6), 13 (IQR: 11-15), and 7 (IQR: 5-9), respectively. Knowledge levels were significantly higher among urban residents and more educated participants, while no significant sex-based difference was observed. Attitude scores were also significantly higher among urban residents and participants with higher educational attainment, whereas no significant associations were observed with age or sex. Although attitudes toward prevention, treatment, screening, and One Health measures were generally positive, preventive practices remained moderate, and risky behaviors such as feeding raw offal to dogs (38.8%) and frequent contact with stray dogs (40.1%) were still common. Knowledge was positively correlated with attitudes and practices, and attitudes were also positively correlated with practices, suggesting that better awareness may support safer preventive behavior. Higher education, urban residence, and absence of stray dog contact predicted higher knowledge, while good practices were associated with higher knowledge, positive attitudes, urban residence, and avoidance of raw offal feeding. In other words, participants who were better informed and had more favorable attitudes were more likely to adopt safer behaviors, whereas risky habits such as feeding raw offal to dogs were linked to poorer preventive practices. These findings provide baseline evidence for targeted community-based interventions and public health strategies to reduce CE transmission in southeastern T & uuml;rkiye, with particular emphasis on rural communities where knowledge gaps and risky practices were more pronounced.
Keywords: Cystic echinococcosis; Knowledge-attitudes-practices; One health; Questionnaire-based survey; Risk factors; T & uuml;rkiye